Crystals and inclined conduits: analogue experiments for slug-driven volcanism - Calleja, Hannah; Pering, Tom (Volcanica, 2023)
Basaltic volcanism is the dominant mode of volcanism on Earth and exhibits a range of activity, from passive degassing to the most common explosive style: strombolian volcanism. Strombolian volcanism is driven by gas slugs, making it vital to consider the effects of variable magmatic rheology and internal vent geometry on slug flow dynamics. Emerging experimental technologies play a major role in developing our understanding of the natural complexity of such basaltic systems. This study examines slug ascent within particle-free and particle-containing media experimentally across a range of inclinations. Dimensionless parameters are derived to describe specific flow characteristics at laboratory and volcanic scales, and to demonstrate the viability of current theoretical framework. Slug ascent is shown to be dependent on its morphology, which is a function of inclination, liquid viscosity, and related controlling characteristics i.e. particle fraction. Maxima for ascent velocities and associated dimensionless parameters occur within the range 40—60°.